Role of peer interaction in social skills development among autistic children within inclusive classrooms - Anee, Farzana Fatima; Ibrahim, Hasniza (Asian Scholars Network, 2025)
Social development is a fundamental aspect of human growth, playing a vital role in shaping an individual’s behaviour, interpersonal relationships, academic success and overall life outcomes. Individuals with autism spectrum disorder (ASD) present with core deficits in social skills. Peer interactions play a crucial role in enhancing social skills among autistic children. This study aimed to examine how peer interaction impacts the social skills development of autistic children within inclusive classroom settings. Using a qualitative research approach, semi-structured interviews were conducted with teachers, parents , and school administrators in inclusive school. The findings revealed that peer engagement fosters improved communication, emotional reciprocity, and social adaptability in autistic children. However, the research also identified several challenges, including social stigma, peer rejection, insufficient awareness among typically developing peers, and limited teacher training and support. The study further explored effective strategies, such as peer modelling, group activities, increased parental involvement, teacher training and counselling support for educators and families. By addressing existing barriers and promoting purposeful peer interaction within inclusive classrooms, education systems can foster a more equitable, socially supportive, and developmentally enriching environment for all learners.